Application of sentinel lymph nodes biopsy tracers for breast cancer after neoadjuvant chemotherapy in China: A multicenter, real-world study - Fengjiang Qu; Tinghan Jiang; Zhenzhen Liu; Rui Ling; Yi Zhao; Hongjian Yang; Yunjiang Liu; Ke Liu; Jianguo Zhang; Dahua Mao; Jianjun He; Zhigang Yu; et al. (iScience, 2025)
Summary: The real-world application of tracers for axillary sentinel lymph node biopsy (SLNB) for breast cancer (BC) after neoadjuvant chemotherapy (NAC) in China was unknown. We analyzed the use of individual tracers or combinations and number of SLNs in patients with BC who underwent SLNB with or without axillary lymph node dissection (ALND) after NAC in 20 hospitals in ten years. A total of 1251 BC patients underwent SLNB or SLNB + ALND after NAC, including 853 (68.2%, 853/1251) with a single tracer, predominantly Methylene blue (MB) (60.1%, 752/1251); and 398 (31.8%, 398/1251) with dual tracers, mainly MB combined with radioisotope (RI) (18.1%, 226/1251).The results showed that the predominance of the MB single-tracer method for SLNB after NAC limits the popularity of SLNB in patients with BC after NAC in China. MB combined with RI is the main dual-tracer method, and detects SLNs more effectively than MB alone.